1968
DOI: 10.2307/2948328
|View full text |Cite|
|
Sign up to set email alerts
|

Cultural Contingencies of Alcoholism: Variations between and within Nineteenth-Century Urban Ethnic Groups in Alcohol-Related Death Rates

Abstract: From the 1890 U.S. Census vital statistics compilations are drawn comparisons of adult rates of death from alcohol-related causes (alcoholism, liver diseases) in urban white ethnic groups (defined by birthplace of mother), with specification of sex, sex and marital status, neighborhood status, and sex and neighborhood status. In each of three cities, the Irish have the highest rate, followed by the English, Germans, and those with U.S.-born mothers, while the Italians and especially Russian Jews have extraordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…esophageal cancer and alcoholic psychoses) among blacks that are distributed similarly to liver cirrhosis [67,68]. Other highly urbanized populations that endured a long period of immigrant status such as Italians and Jews in the U.S. have consistently maintained very low rates of alcoholrelated problems [69]. Furthermore, in parts of the world without a 19th century temperance tradition, rural areas often have higher levels of alcohol consumption than cities [21].…”
Section: Discussionmentioning
confidence: 99%
“…esophageal cancer and alcoholic psychoses) among blacks that are distributed similarly to liver cirrhosis [67,68]. Other highly urbanized populations that endured a long period of immigrant status such as Italians and Jews in the U.S. have consistently maintained very low rates of alcoholrelated problems [69]. Furthermore, in parts of the world without a 19th century temperance tradition, rural areas often have higher levels of alcohol consumption than cities [21].…”
Section: Discussionmentioning
confidence: 99%
“…In any event, whether these two indices constitute two separate measures of alcoholism or are merely two facets of the same measure, it is clear that Ireland has a very low international rank by reference to either. This finding is at variance with the evidence on the Irish in America, where it has been found that 'for both alcoholism and liver disease, the Irish rate is by far the highest' (Room, 1968). However, this study of American mortality statistics was confined to nineteenth century census data, and no more recent material is available.…”
Section: Consumption Of Alcohol Per Personmentioning
confidence: 70%
“…All four skeletons show indicators of musculoskeletal, infectious disease and addictive substance (i.e., tobacco) stressors [155]. While debate persists on the roles of senescence, etiology and coding standards on entheseal pathologies [156–158], male individuals B2 and B3 show rugosity and arthritic changes likely associated with manual labor [11, 159161].…”
Section: Discussionmentioning
confidence: 99%